The diagnostic value of native kidney biopsy in low grade, subnephrotic, and nephrotic range proteinuria: A retrospective cohort study. - Jonathan de Fallois; Soeren Schenk; Jan Kowald; Tom H Lindner; Marie Engesser; Johannes Münch; Christof Meigen; Jan Halbritter (PLoS ONE, 2022)
Background In nephrotic range proteinuria of adult-onset, kidney biopsy is the diagnostic gold standard in determining the underlying cause of disease. However, in low grade or subnephrotic proteinuria the diagnostic value of kidney biopsy as first-line diagnostics is less well established. Methods We conducted a retrospective analysis of all native kidney biopsies at our institution (n = 639) between 01/2012 and 05/2021 for comparison of histological diagnoses and clinical outcomes stratified by amount of proteinuria at the time of kidney biopsy: A: <300mg/g creatinine (low grade), B: 300-3500mg/g creatinine (subnephrotic), C >3500mg/g creatinine (nephrotic). Results Nephrotic range proteinuria was associated with the highest frequency (49.3%) of primary glomerulopathies followed by subnephrotic (34.4%) and low grade proteinuria (37.7%). However, within the subnephrotic group, the amount of proteinuria at kidney biopsy was linearly associated with renal and overall survival (HR 1.05 per Δ100mg protein/g creatinine (95% CI: 1.02-1.09, p = 0.001)) independent of present histological diagnoses and erythrocyturia. Conclusion Frequency of primary glomerulopathies supports to perform kidney biopsy in patients with subnephrotic proteinuria. These patients have a substantial risk of ESKD and death upon follow-up. Therefore, diagnostic accuracy including histopathology is essential to guide personalized treatment and avert detrimental courses.